Disrupted Education: Examining the Experiences of Teachers Transitioning from Face-to-Face to Emergency Remote Teaching during COVID-19 Lockdown - Leonard Busuttil; Colin Calleja; Michelle Attard Tonna (Pensa MultiMedia, 2023)
The COVID-19 lockdown transformed education, forcing teachers accustomed to face-to-face lessons and laboratory use to quickly switch to emergency remote teaching. This study explores how pre-pandemic experience in online learning influenced this transition. Teachers with blended learning experience found it easier to adapt to fully online teaching, despite students' initial enthusiasm for blended learning waning over time. It emerged that students faced a greater workload with online assignments in all subjects. Teachers had to modify their teaching plans, especially for activities requiring laboratories, postponing them until schools reopened. Teachers' feedback highlights the importance of further professional development in online methodologies and investment in digital tools to compensate for the absence of laboratories.